Pemberdayaan Kelompok Tani dalam Pemanfaatan Bakteri Fotosintesis sebagai Pupuk Nabati pada Tanaman Padi - Trisnani Alif; Putri Ayu Ika Setiyowati; Aisyah Hadi Ramadani; Inayah Fitri; Dyah Ayu Sri Hartanti (Pusat Penelitian Pengabdian Pada Masyarakat Sekolah Tinggi Ilmu Tarbiyah Al-Fattah Siman Lamongan, 2023)
The use of anorganic fertilizers is most popular among farmers, the lack of subsidies from the government for anorganic fertilizers so that the scarcity of fertilizers becomes important problem for farmers. The purpose of this activity is to assist farmers in the use of photosynthetic bacteria as fertilizers for plants. The method used is in the form of counseling, and mentoring in the practice of cultivated bacterial photosynthesis for application in fields. The results of the activities showed that before the training the majority of trainees (82.5%) did not know and understand photosynthetic bacterial fertilizers, after training the majority of trainees (80.4%) knew and understood, and were skilled in making and using photosynthetic bacteria. Participation and enthusiasm were shown by the participants during the activity.